Fruit Biology of Coconut (Cocos nucifera L.) - Fernanda Caro Beveridge; Sundaravelpandian Kalaipandian; Chongxi Yang; Steve W. Adkins (Plants, 2022)
Coconut (Cocos nucifera L.) is an important perennial crop adapted to a wide range of habitats. Although global coconut demand has increased sharply over the past few years, its production has been decreasing due to palm senility, as well as abiotic and biotic stresses. In fact, replanting efforts are impeded due to the lack of good quality seedlings. In vitro technologies have a great potential; however, their applications may take time to reach a commercial level. Therefore, traditional seed propagation is still critical to help meet the rising demand and its practice needs to be improved. To achieve an improved propagation via seeds, it is important to understand coconut fruit biology and its related issues. This review aims to provide a comprehensive summary of the existing knowledge on coconut fruit morpho-anatomy, germination biology, seed dispersal, distribution, fruit longevity and storage. This will help to identify gaps where future research efforts should be directed to improve traditional seed propagation.